Moderating Impact of IT Outsourcing Arrangements in a Muslim Country - Ismail, Zuraini (2006)
In recent years, information technology (IT) outsourcing continues to receive favorable acceptance to maximize organization’s benefits. There is evidence showing how partnership quality plays a significant role in achieving overall IT outsourcing success. This research investigates the moderating impact of information technology outsourcing arrangements on the relationship between partnership quality and IT outsourcing success. IT outsourcing arrangements seem to indicate dire need for empirical research. In this study two specific IT outsourcing arrangements are focused on, namely, duration of contract and degree of integration. These arrangements may have different implications on the relationship examined. This research explores and hypothesized such implications. It was tested using a sample from IT managers in 143 Malaysian organizations. Findings and implications of the research are discussed. The findings also provide an insight into IT outsourcing practices in a Muslim country